Keeping the City clean: Exploring the work-related challenges experienced or encountered by Municipal Waste Management Employees in Gauteng - Nteu, Kgotsofalo (My University, 2017)
The increase of people moving from rural areas to major cities has seen a high demand on service delivery from Municipalities, including the effective management of household and commercial waste. Waste management employees play a vital role in ensuring that waste management services are delivered to city residents. This study explored the work-related challenges experienced by Municipal waste management employees. For the purpose of this study, a qualitative research approach that is exploratory in nature was used to guide the study. Non-probability purposive sampling procedures were applied when identifying and recruiting study participants. The sample will consist of 10 participants from 4 job categories, namely, street cleaner, bin loaders, truck drivers and a supervisor as a key informant. In depth semi-structured interviews schedules were used during the data collection process, using a tape-recording tool to collect the data. Thematic content analysis was used to analyze the data collected. This study anticipates to contributing significantly to workplace interventions prepared for employees and adding to the existing social work body of knowledge by enhancing social workers on the challenges encountered by waste management employees and how they can assist through Employee Wellbeing programmes. The findings of this study included challenges that are in relation to the working environment, lack of resources and issues of pertaining the health and safety of employees. Available resources such as wellbeing programmes are available to relieve employees of experienced challenges, however, there is still a need for more research to be done in this field. Key words: Waste management; challenges, work experience, Employee Wellbeing Programmes
In partial fulfilment of the requirements For the degree Bachelor of Social Work